Metode MOORA dalam Sistem Pendukung Keputusan Pemilihan Calon Penerima Bantuan Siswa Miskin (BSM) - Desyanti, Desyanti; Febrina Sari; John Suarlin (STMIK Budi Darma, 2024)
12 years of compulsory education is a government program to increase the nation's intelligence. Since this regulation was implemented, all state schools in Indonesia have not been charged tuition fees. Schools are divided into 2, namely public schools and private schools. Private schools still require students to pay tuition fees. Not all parents are able to pay for their children's school fees due to economic factors. For this reason, the government is trying to provide educational assistance to schools through education offices in the city and province. The Dumai City Education Office provides the Poor Student Assistance (BSM) program to improve the quality of education for the people of Dumai City. This assistance is provided to all students in Dumai City. One of them is MTS A- Imam Abi Yazid, but in the process of providing BSM they still select students based on the school principal's decision so they are not on target. Data on selected students is submitted to the Ministry of Religion to obtain educational assistance without prioritizing students who are truly underprivileged so that students who really need assistance are less likely to receive BSM than other students. Another obstacle is the unavailability of an application for selecting potential recipients of poor assistance so that Businesses have difficulty collecting data on students who really need scholarships. For this reason, we need a system that is capable of filtering data on students who are truly underprivileged. The Moora method is able to solve this problem, because it is a decision support system method that has a level of flexibility. The results of this research can be seen from 20 students, 10 students were at the top with the highest score of 0.1182